Prevention and management of infection associated with transrectal ultrasound guided prostate biopsy in Ireland - Ni Bhuachalla, Cliodhna Frances; Nolan, Eileen; Galvin, David; Buckley, Claire M; Fitzpatrick, Fidelma (International Journal of Infection Control, 2015)
The incidence of transrectal ultrasound (TRUS)–guided prostate biopsy associated infection is reportedly increasing, particularly antimicrobial resistant (AMR) infections. To inform development of an inaugural national policy on prevention and management of infection post TRUS biopsy, we conducted a national survey of ten prostate cancer centres that perform approximately 90% of public prostate biopsies in Ireland. An on-line questionnaire regarding prostate biopsy pathways, pre-biopsy AMR risk assessment and antimicrobial prophylaxis regimens, and post-biopsy infection surveillance and management was circulated to all centres. Data from 1st January 2011 to 30th June 2013 were collected retrospectively from July to September 2013. Data were analysed using Microsoft Excel® software. The results of this survey demonstrated marked variation of practices nationally. Three centres reported risk assessing for AMR colonisation pre-biopsy. AMR screening was not conducted routinely in any centre. Antimicrobial prophylaxis regimens, surveillance programmes and empiric therapy guidelines for sepsis also varied between centres. A range of infectious complications were reported, both bloodstream infection (BSI) and non-BSI, however, due to use of non-standardised case definitions, national infection rates could not be generated. At the time of the survey, there were no Irish guidelines and centres followed American and/or European guidelines. Following our survey the National Cancer Control Programme published a “National Policy on the Prevention and Management of Infection post Transrectal Ultrasound-guided Prostate Biopsy” in June 2014 to assist in standardising practice and reducing risk of infectious complications.